Analisis Persepsi Pihak Industri terhadap Kompetensi Mahasiswa PTM pada Program Magang Industri - Risa Tri Komala Sari; Yuyun Estriyanto (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2025)
⚠️Notice: This article has been identified as a duplicate publication of the following article published in another journal:Persepsi Pihak Industri Terhadap Kompetensi Mahasiswa PTM pada Program Magang Industri Nozel : Jurnal Pendididikan Teknik Mesin (https://jurnal.uns.ac.id/nozel/article/view/90595)Based on internal verification, the authors did not request withdrawal and did not notify the JIPTEK Editorial Office that the manuscript had been submitted to another journal. This constitutes a violation of publication ethics, particularly regarding simultaneous submission and redundant publication, as outlined by the Committee on Publication Ethics (COPE) and JIPTEK’s editorial policy.Accordingly, the Editorial Board declares this article as a duplicate publication. The article will remain available on the JIPTEK website to maintain the transparency and integrity of the scholarly record, accompanied by this official notice.The Editorial Board of JIPTEK reaffirms its commitment to upholding academic integrity and strongly urges all authors to adhere to ethical publication standards at all stages of the submission and publication process.